KEMAMPUAN SISWA MENGANALISIS UNSUR INTRINSIK DALAM CERITA LEGENDA “SI LANCANG” KELAS V GUGUS I HANG NADIM KECAMATAN TAMPAN KOTA PEKANBARU - Novita, Ririn Novita Ririn; Noviana, Eddy Noviana Eddy; Kurniaman, Otang Kurniaman Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Analyzing the intrinsic elements in the legend can be useful for elementary school children. In the curriculum of primary school students were told to look for elements that build up a work of literature that is character, disposition, setting, theme, viewpoint and mandate. But in primary school are still many students who have not been able to identify the intrinsic elements. This research was done to determine the student's ability to analyze the intrinsic elements of the legend